Plasticizer exposure in Germany from 1988 to 2022: Human biomonitoring data of 20 plasticizers from the German Environmental Specimen Bank - Monika Kasper-Sonnenberg; Claudia Pälmke; Sonja Wrobel; Thomas Brüning; Aline Murawski; Petra Apel; Till Weber; Marike Kolossa-Gehring; Holger M. Koch (Environment International)
The German Environmental Specimen Bank (ESB) annually archives 24-h urine samples since the early 1980s. In this study, we analyzed 420 of these samples from the years 2014 to 2022 for metabolites of 18 phthalates and two substitutes. We merged the new data with the data from previous measurement campaigns to a combined dataset of 1825 samples covering a 35-year period from 1988 to 2022 to investigate time trends, calculate daily intakes and perform an anti-androgenic mixture risk assessment. With the extended set of 41 biomarkers, we are now able to monitor the exposure to all EU-labelled reprotoxic phthalates. Most phthalate exposures continued to decrease since first measurements in the 80s, with biggest drops for DnBP (96.6 %) and DEHP (90.9 %). DiNP and DiDP, seen on the rise in earlier campaigns, now declined. Exposures to the newly included, reprotoxic phthalates were generally negligible. Regarding mixture risk, 5 % of the highly exposed still exceeded the Hazard Index (HI) of 1 in 2009. In the current measurement campaign only three individuals (0.7 %) exceeded the HI of 1 (with exceedances still driven by DEHP and DnBP).In 2022, 20 % of the individuals still had an HI > 0.2, which we propose as a benchmark for interpreting phthalate mixture risk, considering concurrent exposures to other anti-androgens. Exposure to the substitutes DINCH and DEHTP continues to increase, with daily intakes of DEHTP exceeding those of DEHP since 2018. Compared with the United States (US) National Health and Nutrition Examination Survey (NHANES) phthalate exposures seem to align, except for DEHTP with up to ten times higher levels in the US. Human biomonitoring (HBM) is the ideal tool to capture actual mixture exposures per individual, integrating all external exposure sources and pathways, thus we will continue to use HBM in exposure and risk assessment of phthalates and other (anti-androgenic) chemicals.